The stones of the Parthenon - Korres, Manolis. (Athens)
69 sayfa
Keywords: “The Stones of the Parthenon is a compelling volume that explores the astonishing technological achievements that made possible the assembly of stones on the Acropolis. This readable account tells how an eleven-ton Doric column capital was quarried and transported to Athens, epitomizing the achievements of the remarkable craftsmen who built the Parthenon. The author's intricate line drawings clearly show the methods and tools used to achieve this feat.“--